SEA-FLOOR SPREADING IN THE KOMANDORSKIY BASIN AND STRUCTURE OF THE SHIRSHOV RIDGE - Muzurov Ye.L.; Baranov B.V.; Borisenko Yu.V.; Brudastov P.L.; Litvinova L.A. (My University, 1989)
The Komandorskiy Basin in the western Bering Sea is bounded on the south by the Komandorskiy segment of the Aleutian island arc and on the east by the Shirshov Ridge, and is regarded as a marginal basin of the type formed by back-arc spreading. In one tectonic scheme, its spreading is assumed to have been diffuse. Other authors support the view that there is one spreading axis, either with a northwest strike, or with a northwest strike in the southern part of the basin and a submeridional near its center. We propose a new structural scheme of sea-floor spreading with its axis oriented submeridionally to the northeast. It is based on a summary and analysis of CDP reflection data. We also used earlier published data of single-channel seismic profiling.